HISTORICAL POLICY OF THE CZECH REPUBLIC AND SLOVAKIA: EXPERIENCE AND PRACTICES - SLYUSAR , Vadym; MOSIENKO, Oleksandr (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research – using the example of the Czech Republic and Slovakia to reveal the features of the policy of historical memory, developed in the process of “overcoming the past” in the countries of Central and Eastern Europe. Methodology: General scientific methods (analysis, synthesis, comparison, generalization) were used to collect information and analyze it. The scientific novelty consists in the fact that, based on the collected materials, the peculiarities of the historical policy of the Czech Republic and Slovakia have been analyzed; common and distinctive features of such policies have been traced; the creation aspects of special organizations engaged in memory policy have been noted, in particular, the Institute of National Memory (Ústav pamäti národa) in Slovakia as a participant in the revision of the history of World War II and the role of the Institute for the Study of Authoritarian Regimes (Ústav pro studium totalitních režimů) in the Czech Republic; the conclusions have been drawn about the strategies for the development and functioning of models of historical policy of Slovakia and the Czech Republic in a comparative perspective. Conclusions. Over the past three decades, the communist theme has remained a priority for the Czech and Slovak historical policy, despite the diversity of other aspects. The analysis of the activities of the Memory of the People project and special organizations shows that the focus is mainly on the memory of the crimes of the communist regime. The researchers note the success of the historical policy of the Czech Republic and Slovakia, which is indirectly confirmed by the achievements of both countries after joining the European Union. The main topics in the Czech and Slovak political and social discourse are the topics related to World War II, the Nazi occupation, the Soviet period, the period of the collapse of Czechoslovakia and the modern life of countries within the European Union. In the Czech Republic and Slovakia the historical memory policy on these topics is not limited only to the participation of the aforementioned institutions and the concepts put forward by them. The study of the past is manifested in the decommunization of history, the dismantling of Soviet monuments, as well as active discussions in the media. The role of these discussions in the historical policy formation is significant and requires further study. Keywords: historical politics, politics of memory, the Czech Republic, Slovakia, international relations.